Layered composite metal hydroxide and preparation method thereof, layered metal catalyst and preparation method thereof, and preparation method of carbon nanotube
Through blending and pH adjustment methods, the assembly structure of layered composite metal hydroxides was successfully regulated, solving the complex regulation problems in the prior art, and realizing the preparation of catalysts suitable for carbon nanotube growth, with simple operation and easy operation Advantages of magnification.
Patent Information
- Application Number
- CN202510013613.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the assembly structure regulation method of layered composite metal hydroxide is complex and difficult to be applicable to carbon nanotube growth systems.
By blending soluble divalent metal ions, soluble trivalent metal ions and soluble hexavalent metal acids in a solvent, adjusting the pH to 6-11, and reacting at 25-150°C, the layered composite metal hydroxide was obtained after drying. to realize the regulation of its assembly structure.
The assembly structure regulation of layered composite metal hydroxide is realized, and it is simple to operate and is easy to amplify. It is suitable for binary, ternary and quadrimer layered composite metal hydroxide systems, and can be used to catalyze relatively rigid multi-wall carbon nanometers. Growth of tubes and flexible, less-walled, single-walled carbon nanotubes.
Smart Images

Figure CN119406419A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to a layered composite metal hydroxide and a preparation method thereof, a layered metal catalyst and a preparation method thereof, and a preparation method of carbon nanotubes. Background Art
[0002] As a new type of material, carbon nanotubes have excellent mechanical properties, electrical conductivity, thermal properties and stable chemical properties. They have broad application prospects in the fields of composite material reinforcement, electrochemical energy storage, electronic devices, etc. and have attracted much attention. At present, the most suitable method for the large-scale growth of carbon nanotubes is to grow them in a fluidized bed with the help of catalyst powder by chemical vapor deposition. Among them, the selection of catalyst system is particularly important for the efficient and high-quality growth of carbon nanotubes. Studies have shown that the catalyst needs to have a layered structure of appropriate size and a relatively flat surface, so as to provide a flat substrate of a certain size for the growth of carbon nanotubes, which is conducive to the increase of carbon nanotube length and may even grow in a long array structure; in addition, the catalyst needs to have a high specific surface area, so as to increase the loading amount and utilization rate of active metals, thereby increasing the yield of carbon nanotubes.
[0003] In addition, the assembly structure of the catalyst layer has a great influence on the growth of different types of carbon nanotubes. Multi-walled carbon nanotubes have strong rigidity and can hold surrounding objects apart when forming an array structure. Therefore, even if the catalyst layers are in a stacked structure, the growth of multi-walled carbon nanotubes is less affected. In contrast, few-walled and single-walled carbon nanotubes are flexible. When the catalyst layers are stacked severely or even completely agglomerated, the extension of the few / single-walled carbon nanotubes will be restricted, and the few / single-walled carbon nanotubes will be intertwined and self-poisoned, thus stopping their growth. Only when a single catalyst layer is fully exposed can the active metal of the catalyst fully contact the reaction gas, and the carbon nanotubes can fully extend and grow.
[0004] Among layered materials, layered composite metal hydroxides are excellent catalyst precursors for growing carbon nanotubes. However, the current methods for regulating the assembly structure of layered composite metal hydroxides still have the following problems: the regulation method is relatively complex and difficult to use in carbon nanotube growth systems. It is urgent to develop a layered composite metal hydroxide based on which a layered metal catalyst with controllable assembly structure can be prepared for carbon nanotube growth to solve the above problems. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the purpose of the present invention is to provide a layered composite metal hydroxide and a preparation method thereof, a layered metal catalyst and a preparation method thereof, and a preparation method of carbon nanotubes. The preparation method of the layered composite metal hydroxide of the present invention has the advantages of simple operation, easy amplification, and good control effect.
[0006] To this end, the first aspect of the present invention provides a method for preparing a layered composite metal hydroxide, comprising the following steps: Mixing soluble divalent metal ions, soluble trivalent metal ions and soluble hexavalent metal acid radicals in a solvent, adjusting the pH to 6-11; reacting at 25-150°C; drying to obtain a layered composite metal hydroxide; The soluble hexavalent metal acid radicals include tungstate and / or molybdate; The blending is carried out under stirring conditions; the stirring speed is 1 rpm-600 rpm.
[0007] The present invention achieves the purpose of regulating the number of crystal nucleation and crystal growth sites by controlling raw materials, regulating reaction temperature, and pH parameters, thereby realizing the regulation of the assembly structure of the layered composite metal hydroxide, and realizing the assembly structure of the layered composite metal hydroxide sheets stacked, partially stacked, cross-grid, and mutually discrete. Compared with the existing regulation means, the present invention has the advantages of simple operation, easy amplification, and good regulation effect. It can be used as a catalyst to prepare carbon nanotubes in the future, specifically, for the catalytic growth of relatively rigid multi-walled carbon nanotubes, and can also provide sufficient space for the catalytic growth of relatively flexible few-walled and single-walled carbon nanotubes.
[0008] The preparation method of the layered composite metal hydroxide of the present invention is widely applicable to binary, ternary and quaternary layered composite metal hydroxide systems.
[0009] In some embodiments of the present invention, the soluble divalent metal ions include Mg 2+ 、Zn 2+ , Ca 2+ , Mn 2+ , Fe 2+ 、Co 2+ 、Ni 2+ and Cu 2+ At least one of .
[0010] In some embodiments of the present invention, the soluble trivalent metal ions include Cr 3+ 、Al 3+ 、Ru 3+ , Fe 3+ 、Co 3+ At least one of .
[0011] In some embodiments of the present invention, the molar ratio of the soluble divalent metal ions to the soluble trivalent metal ions is (0.1-10):1.
[0012] In some embodiments of the present invention, the molar ratio of the soluble divalent metal ions to the soluble hexavalent metal acid radicals is (1-10): (0.001-1).
[0013] In some embodiments of the present invention, the reaction time is 0.1 h-36 h.
[0014] In some preferred embodiments of the present invention, the soluble divalent metal ions include a first soluble divalent metal ion and a second soluble divalent metal ion; The first soluble divalent metal ion includes Fe 2+ 、Co 2+ 、Ni 2+ and Cu 2+ At least one of; The second soluble divalent metal ion comprises Mg 2+ 、Zn 2+ , Ca 2+ , Mn 2+ At least one of .
[0015] In some preferred embodiments of the present invention, the soluble trivalent metal ions include a first soluble trivalent metal ion and a second soluble trivalent metal ion; The first soluble trivalent metal ion includes Ru 3+ , Fe 3+ 、Co 3+ At least one of; The second soluble trivalent metal ion includes Cr 3+ 、Al 3+ At least one of .
[0016] In some preferred embodiments of the present invention, the molar ratio of the first soluble divalent metal ion to the second soluble divalent metal ion is (0.002-1):1.
[0017] In some preferred embodiments of the present invention, the molar ratio of the first soluble trivalent metal ion to the second soluble trivalent metal ion is (0.002-1):1.
[0018] The second aspect of the present invention provides a layered composite metal hydroxide obtained by the above-mentioned method for preparing a layered composite metal hydroxide.
[0019] In some embodiments of the present invention, the flake diameter of the layered composite metal hydroxide is 0.5 μm-10 μm.
[0020] In some embodiments of the present invention, the thickness of the layered composite metal hydroxide is 5 nm to 200 nm.
[0021] In some embodiments of the present invention, the bulk density of the layered composite metal hydroxide is 0.01 g / cm 3 -0.20 g / cm 3 .
[0022] The third aspect of the present invention provides a method for preparing a layered metal catalyst, comprising the following steps: The layered composite metal hydroxide is calcined and reduced at 400-1000°C to obtain a layered metal catalyst.
[0023] In some embodiments of the present invention, the method for preparing the layered metal catalyst specifically comprises the following steps: The layered composite metal hydroxide is calcined at a heating rate of 1°C / min-20°C / min to 400°C-1000°C, and then reduced to obtain a layered metal catalyst.
[0024] In some embodiments of the present invention, the reducing agent used in the reduction comprises at least one of hydrogen, methane, and carbon monoxide.
[0025] In some embodiments of the present invention, the calcination time is 20 min-1440 min.
[0026] In some embodiments of the present invention, the reduction time is 1 min to 60 min.
[0027] The fourth aspect of the present invention provides a layered metal catalyst prepared by the above-mentioned method for preparing a layered metal catalyst.
[0028] In some embodiments of the present invention, the layer diameter of the layered metal catalyst is 1 μm-50 μm.
[0029] In some embodiments of the present invention, the surface density of the metal particles supported on the layered metal catalyst is 10 12 m -2 -10 16 m -2 .
[0030] A fifth aspect of the present invention provides a method for preparing carbon nanotubes, comprising the following steps: At 500°C-1000°C, a carbon source is decomposed to deposit carbon nanotubes on the layered metal catalyst; the layered metal catalyst is removed to obtain carbon nanotubes; the length of the carbon nanotubes is 0.5-50 μm.
[0031] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 shows a typical scanning electron microscope photograph of the layered composite metal hydroxide prepared in Example 1; Figure 2 shows a typical scanning electron microscope photograph of the layered composite metal hydroxide prepared in Example 2; Figure 3 shows a typical scanning electron microscope photograph of the layered composite metal hydroxide prepared in Example 4; Figure 4 shows a typical scanning electron microscope photograph of the layered composite metal hydroxide prepared in Example 5; Figure 5 shows a typical scanning electron microscope image of the carbon nanotubes prepared in Example 5; Figure 6 A typical scanning electron microscope photograph of the layered composite metal hydroxide prepared in Comparative Example 1 is shown; Figure 7 A typical transmission electron microscope photograph of the layered composite metal hydroxide prepared in Comparative Example 2 is shown; Figure 8 A typical scanning electron microscope photograph of the layered composite metal hydroxide prepared in Comparative Example 3 is shown; Fig. 9 A typical scanning electron microscope photograph of the layered composite metal hydroxide prepared in Comparative Example 4 is shown; Fig.10 A typical transmission electron microscope photograph of the layered composite metal hydroxide prepared in Comparative Example 5 is shown. DETAILED DESCRIPTION
[0033] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0034] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0035] The first aspect of the present invention provides a method for preparing a layered composite metal hydroxide, comprising the following steps: Mixing soluble divalent metal ions, soluble trivalent metal ions and soluble hexavalent metal acid radicals in a solvent, adjusting the pH to 6-11; reacting at 25-150°C; drying to obtain a layered composite metal hydroxide; The soluble hexavalent metal acid radicals include tungstate and / or molybdate; The blending is carried out under stirring conditions; the stirring speed is 1 rpm-600 rpm.
[0036] The present invention achieves the purpose of regulating the number of crystal nucleation and crystal growth sites by controlling raw materials, regulating reaction temperature, and pH parameters, thereby realizing the regulation of the assembly structure of the layered composite metal hydroxide, and realizing the assembly structure of the layered composite metal hydroxide sheets stacked, partially stacked, cross-grid, and mutually discrete. Compared with the existing regulation means, the present invention has the advantages of simple operation, easy amplification, and good regulation effect. It can be used as a catalyst to prepare carbon nanotubes in the future, specifically, for the catalytic growth of relatively rigid multi-walled carbon nanotubes, and can also provide sufficient space for the catalytic growth of relatively flexible few-walled and single-walled carbon nanotubes.
[0037] The preparation method of the layered composite metal hydroxide of the present invention is widely applicable to binary, ternary and quaternary layered composite metal hydroxide systems.
[0038] In some preferred embodiments of the present invention, soluble divalent metal ions, soluble trivalent metal ions and soluble hexavalent metal acid radicals are mixed in a solvent, the pH is adjusted to 6-11, reacted at 25-95° C., and dried to obtain a layered composite metal hydroxide.
[0039] In some preferred embodiments of the present invention, soluble divalent metal ions, soluble trivalent metal ions and soluble hexavalent metal acid radicals are mixed and the pH is adjusted to 7-11.
[0040] In some preferred embodiments of the present invention, the solvent may be a liquid having a diluting effect on soluble divalent metal ions, soluble trivalent metal ions and soluble hexavalent metal acid radicals, for example, may be water.
[0041] In some embodiments of the present invention, the soluble divalent metal ions include Mg 2+ 、Zn 2+ , Ca 2+ , Mn 2+ , Fe 2+ 、Co 2+ 、Ni 2+ and Cu 2+ At least one of .
[0042] In some preferred embodiments of the present invention, the soluble divalent metal ions include a first soluble divalent metal ion and a second soluble divalent metal ion; The first soluble divalent metal ion includes Fe 2+ 、Co 2+ 、Ni 2+ and Cu 2+ At least one of; The second soluble divalent metal ion comprises Mg 2+ 、Zn 2+ , Ca 2+ , Mn 2+ At least one of .
[0043] In some preferred embodiments of the present invention, the molar ratio of the first soluble divalent metal ion to the second soluble divalent metal ion is (0.002-1):1. As an example, the molar ratio of the first soluble divalent metal ion to the second soluble divalent metal ion can be 0.002:1, 0.003:1, 0.004:1, 0.005:1, 0.006:1, 0.007:1, 0.008:1, 0.009:1, 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1 or 1:1, or can be a range consisting of any of the above numerical values.
[0044] In some embodiments of the present invention, the soluble divalent metal ions are present in the form of soluble divalent metal salts; the anions in the soluble divalent metal salts include Cl - 、NO3 - 、SO4 2- , acetate.
[0045] In some embodiments of the present invention, the soluble trivalent metal ions include Cr 3+ 、Al 3+ 、Ru 3+ , Fe 3+ 、Co 3+ At least one of .
[0046] In some preferred embodiments of the present invention, the soluble trivalent metal ions include a first soluble trivalent metal ion and a second soluble trivalent metal ion; The first soluble trivalent metal ion includes Ru 3+, Fe 3+ 、Co 3+ At least one of; The second soluble trivalent metal ion includes Cr 3+ 、Al 3+ At least one of .
[0047] In some preferred embodiments of the present invention, the molar ratio of the first soluble trivalent metal ion to the second soluble trivalent metal ion is (0.002-1):1. As an example, the molar ratio of the first soluble trivalent metal ion to the second soluble trivalent metal ion can be 0.002:1, 0.003:1, 0.004:1, 0.005:1, 0.006:1, 0.007:1, 0.008:1, 0.009:1, 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1 or 1:1, or can be a range consisting of any of the above numerical values.
[0048] In some embodiments of the present invention, the soluble trivalent metal ions include Ru 3+ , Fe 3+ 、Co 3+ At least one of .
[0049] In some embodiments of the present invention, the soluble trivalent metal ion exists in the form of a soluble trivalent metal salt; the anion in the soluble trivalent metal salt includes Cl - 、NO3 - 、SO4 2- , acetate.
[0050] In some embodiments of the present invention, the soluble hexavalent metal acid radical exists in the form of a soluble hexavalent metal acid salt; the soluble hexavalent metal acid salt includes ammonium molybdate and / or sodium molybdate.
[0051] In some embodiments of the present invention, the molar ratio of the soluble divalent metal ions to the soluble trivalent metal ions is (0.1-10): 1, preferably (0.5-3): 1; in other embodiments of the present invention, the molar ratio of the divalent to trivalent metal ions is 0.6:1, 2.2:1, 2.4:1 or 1.2:1.
[0052] In some embodiments of the present invention, the molar ratio of the soluble divalent metal ions to the soluble hexavalent metal acid radicals is (1-10):(0.001-1). In other embodiments of the present invention, the molar ratio of the soluble divalent metal ions to the soluble hexavalent metal acid radicals is 5.3:0.1, 6:0.1, 1:0.01, 1.1:0.01 or 4:1.
[0053] In some embodiments of the present invention, the reaction time is 0.1 h-36 h.
[0054] In some embodiments of the present invention, the stirring speed is preferably 300 rpm-500 rpm.
[0055] In some embodiments of the present invention, the drying temperature is 80°C-90°C.
[0056] In some embodiments of the present invention, the mixing specifically comprises: Mix soluble divalent metal ions, soluble trivalent metal ions and solvent, adjust the pH to 6-11, and obtain a first mixed solution; mix soluble hexavalent metal acid radicals and solvent to obtain a second mixed solution; mix the first mixed solution and the second mixed solution, and adjust the pH to 6-11.
[0057] In some embodiments of the present invention, an alkaline substance is used to adjust the pH; the alkaline substance is preferably present in the form of a solution, and the concentration of the alkaline substance in the solution is 0.1 mol / L-20 mol / L.
[0058] In some embodiments of the present invention, the alkaline substance includes at least one of sodium hydroxide, potassium hydroxide, sodium bicarbonate, sodium carbonate, ammonium bicarbonate, ammonium carbonate, urea and ammonia water.
[0059] In some embodiments of the present invention, the method for preparing the first mixed solution specifically includes: mixing soluble divalent metal ions, soluble trivalent metal ions and a solvent to obtain a metal ion solution, and mixing the metal ion solution with an alkaline substance until the pH of the system is 6-11.
[0060] In some embodiments of the present invention, the concentration of metal ions in the metal ion solution is 0.005 mol / L - 2 mol / L.
[0061] The second aspect of the present invention provides a layered composite metal hydroxide obtained by the above-mentioned method for preparing a layered composite metal hydroxide.
[0062] The method of the present invention can successfully prepare different types of assembly structures, including stacked, partially stacked, crossed grid and discrete sheet structures. Among them, the bulk density of the grid-like layered composite metal hydroxide powder is relatively low, and the grid structure provides an initial growth space for carbon nanotubes, and the carbon nanotubes catalytically grown thereon are easy to extend. The bulk density of the discrete sheet-like layered composite metal hydroxide powder is even lower, which is not only conducive to strengthening the mass transfer and heat transfer process in the reactor, but also the sheets are separated and easy to push apart, and will not split the complete growth structure of the carbon nanotubes.
[0063] In some embodiments of the present invention, the flake diameter of the layered composite metal hydroxide is 0.5 μm-10 μm.
[0064] In some embodiments of the present invention, the thickness of the layered composite metal hydroxide is 5 nm to 200 nm.
[0065] In some embodiments of the present invention, the bulk density of the layered composite metal hydroxide is 0.01 g / cm 3 -0.20 g / cm 3 .
[0066] The third aspect of the present invention provides a method for preparing a layered metal catalyst, comprising the following steps: The layered composite metal hydroxide is calcined at a heating rate of 1°C / min-20°C / min to 400°C-1000°C, and then reduced to obtain a layered metal catalyst.
[0067] In some embodiments of the present invention, the reducing agent used in the reduction comprises at least one of hydrogen, methane, and carbon monoxide.
[0068] In some embodiments of the present invention, calcination is performed in the presence of air or a protective gas; the protective gas may include at least one of hydrogen, nitrogen or argon.
[0069] In some embodiments of the present invention, the calcination time is 20 min-1440 min.
[0070] In some embodiments of the present invention, the reduction time is 1 min to 60 min.
[0071] The fourth aspect of the present invention provides a layered metal catalyst prepared by the above-mentioned method for preparing a layered metal catalyst.
[0072] The layered metal catalyst prepared by the present invention is suitable for catalytic growth of carbon nanotubes, specifically, for catalytic growth of relatively rigid multi-walled carbon nanotubes, and can also provide sufficient space for catalytic growth of relatively flexible few-walled and single-walled carbon nanotubes.
[0073] In some embodiments of the present invention, the layer diameter of the layered metal catalyst is 1 μm-50 μm.
[0074] In some embodiments of the present invention, the surface density of the metal particles supported on the layered metal catalyst is 10 12 m -2 -10 16 m -2 .
[0075] A fifth aspect of the present invention provides a method for preparing carbon nanotubes, comprising the following steps: At 500°C-1000°C, a carbon source is decomposed to deposit carbon nanotubes on the layered metal catalyst; the layered metal catalyst is removed to obtain carbon nanotubes; the length of the carbon nanotubes is 0.5-50 μm.
[0076] In some embodiments of the present invention, the decomposition time is 30 min to 150 min.
[0077] In some embodiments of the present invention, the flow rate of the carbon source is 0.1 L / min-0.5 L / min.
[0078] In some embodiments of the present invention, the carbon source includes at least one of methane, methanol, ethylene, ethane, ethanol, propylene, propane, carbon monoxide, natural gas, liquefied petroleum gas, cyclohexane, n-hexane, benzene or toluene. The carbon source of the present invention has a wide range of sources.
[0079] In some embodiments of the present invention, the method for preparing carbon nanotubes further comprises: decomposing the carbon source in the presence of a protective gas; the protective gas may include at least one of hydrogen, nitrogen or argon.
[0080] In some embodiments of the present invention, the layered metal catalyst is removed using an acid.
[0081] The scheme of the present disclosure will be explained below in conjunction with the examples. Those skilled in the art will appreciate that the following examples are only used to illustrate the present disclosure and should not be considered to limit the scope of the present disclosure. Where specific techniques or conditions are not indicated in the examples, the techniques or conditions described in the literature in this area or the product instructions are used. Where the manufacturers of reagents or instruments are not indicated, they are all conventional products that can be obtained commercially.
[0082] Example 1 The preparation method of the layered metal catalyst of this embodiment comprises the following steps: (1) Dissolve 0.1 mol magnesium sulfate, 0.04 mol aluminum sulfate, and 0.04 mol ferric sulfate in 1 L of water and stir to form solution A. Dissolve 0.001 mol ammonium molybdate in water and stir to form solution B. Dissolve 0.5 mol sodium bicarbonate in water and stir to form solution C.
[0083] (2) Solution A was added dropwise to solution C at a rate of 5 mL / min until the pH was 8-10 to obtain a mixed solution of A and C. Solution B was added dropwise to the mixed solution of A and C, and the mixture was stirred at 50 °C and 500 rpm for 10 h. Subsequently, the mixture was aged at 50 °C for 6 h. After the reaction was completed, the product was filtered and washed to neutrality. The solid was dried at 80 °C in a forced air drying oven and ground to obtain a layered composite metal hydroxide with stacked layers. The size of the layer assembly was more than 10 μm, and the powder bulk density was 0.18 g / cm 3 .like Figure 1 shown.
[0084] (3) 0.5 g of layered composite metal hydroxide was placed in a fixed bed reactor, 0.5 L / min of nitrogen was introduced, the temperature was raised to 700 °C, calcined for 60 min, and then 0.2 L / min of hydrogen was introduced for reduction for 10 min to obtain a layered metal catalyst with an Fe particle surface density of 5×10 14 m -2 .
[0085] The method for preparing carbon nanotubes of this embodiment comprises the following steps: The layered metal catalyst was placed in a fixed bed reactor, and 0.5 L / min ethylene was introduced at 700 °C for 30 min to prepare carbon nanotubes. After the reaction was completed, the temperature was lowered to room temperature under inert gas protection, and the black fluffy product was collected. The obtained carbon nanotubes grew in a multi-walled array structure with a length of 2-50 μm.
[0086] Example 2 The preparation method of the layered metal catalyst of this embodiment comprises the following steps: (1) Dissolve 0.1 mol magnesium nitrate, 0.04 mol aluminum nitrate, 0.01 mol iron nitrate and 0.01 mol cobalt nitrate (Co(NO3)2) in 1 L of water and stir to form solution A. Dissolve 0.001 mol ammonium molybdate in water and stir to form solution B. Dissolve 0.42 mol sodium hydroxide in water and stir to form solution C.
[0087] (2) Solution C was added dropwise to solution A at a rate of 10 mL / min until the end point pH was 8-10, and then the reaction temperature was set to 80 °C, the stirring speed was 300 rpm, and the reaction was continued for 6 h. Solution B was added dropwise to the mixed solution of A and C, and the pH was still 8-10. The stirring reaction was continued for 4 h under the same conditions. Subsequently, it was allowed to stand and age at 80 °C for 12 h. After the reaction was completed, the product was filtered and washed to neutrality. The solid was dried at 80 °C in a forced air drying oven and ground to obtain a layered composite metal hydroxide with stacked layers. The size of the layer assembly was ≤5 μm and the powder bulk density was 0.09 g / cm 3 .like Figure 2 shown.
[0088] (3) 0.5 g of layered composite metal hydroxide was placed in a fixed bed reactor, 0.5 L / min nitrogen was introduced, the temperature was raised to 650 °C, calcined for 20 min, and then 0.2 L / min hydrogen was introduced for reduction for 10 min to obtain a layered metal catalyst with a total surface density of 6×10 Fe and Co particles. 14 m -2 .
[0089] The method for preparing carbon nanotubes of this embodiment comprises the following steps: The layered metal catalyst was placed in a fixed bed reactor, and 0.5 L / min ethylene was introduced at 650 °C for 60 min to prepare carbon nanotubes. After the reaction was completed, the temperature was lowered to room temperature under inert gas protection, and the black fluffy product was collected. The obtained carbon nanotubes grew in a few-wall array structure with a length of 5-20 μm.
[0090] Example 3 The preparation method of the layered metal catalyst of this embodiment comprises the following steps: (1) Dissolve 0.6 mol zinc sulfate, 0.2 mol aluminum nitrate, and 0.05 mol ferric nitrate in 1 L of water and stir to form solution A. Dissolve 0.01 mol ammonium molybdate in water and stir to form solution B. Dissolve 2.2 mol sodium hydroxide in water and stir to form solution C.
[0091] (2) Solution A was added dropwise to solution C at a rate of 20 mL / min until the end point pH was 8-11, and then the reaction temperature was set to 25 °C, the stirring speed was set to 300 rpm, and the reaction was continued for 2 h. Solution B was added dropwise to the mixed solution of A and C, and the pH was still 8-11. The stirring reaction was continued for 8 h under the same conditions. Subsequently, the mixture was allowed to stand and age for 24 h at 25 °C. After the reaction was completed, the product was filtered and washed to neutrality. The solid was dried at 80 °C in a forced air drying oven and ground to obtain a layered composite metal hydroxide with stacked layers. The size of the layer assembly was more than 10 μm, and the powder bulk density was 0.21 g / cm 3 .
[0092] (3) 0.5 g of layered composite metal hydroxide was placed in a fixed bed reactor, 0.5 L / min nitrogen was introduced, the temperature was raised to 750 °C, calcined for 75 min, and then 0.2 L / min carbon monoxide was introduced for reduction for 10 min to obtain a layered metal catalyst with an Fe particle surface density of 1×10 15 m -2 .
[0093] The method for preparing carbon nanotubes of this embodiment comprises the following steps: The layered metal catalyst was placed in a fixed bed reactor, and 0.5 L / min propylene was introduced at 750 °C for 45 minutes to prepare carbon nanotubes. After the reaction was completed, the temperature was lowered to room temperature under inert gas protection, and the black fluffy product was collected. The obtained carbon nanotubes grew in a single-walled mesh cluster structure with a length of 0.5-2 μm.
[0094] Example 4 The preparation method of the layered metal catalyst of this embodiment comprises the following steps: (1) Dissolve 0.01 mol magnesium sulfate, 0.005 mol chromium sulfate, 0.001 mol cobalt sulfate, and 0.001 mol nickel sulfate in 1 L of water and stir to form solution A. Dissolve 0.003 mol sodium molybdate in water and stir to form solution B. Dissolve 0.046 mol NH3·H2O in water and stir to form solution C.
[0095] (2) Solution A and solution C were added dropwise at a rate of 6 mL / min until the end point pH was 7-10. The reaction temperature was set to 115 °C, the stirring speed was 300 rpm, and the reaction was continued for 2 h. Solution B was added dropwise to the mixed solution of A and C. The pH was still 7-10. The stirring reaction was continued for 8 h under the same conditions. Subsequently, the mixture was allowed to stand for 10 h at 115 °C. After the reaction was completed, the product was filtered and washed to neutrality. The solid was dried at 80 °C in a forced air drying oven and ground to obtain a layered composite metal hydroxide with separate lamellar layers and no obvious lamellar assembly. The bulk density of the powder was 0.02 g / cm 3 .like Figure 3 shown.
[0096] (3) 0.5 g of layered composite metal hydroxide was placed in a fixed bed reactor, 0.5 L / min nitrogen was introduced, the temperature was raised to 800 °C, calcined for 120 min, and then 0.2 L / min methane was introduced for reduction for 10 min to obtain a layered metal catalyst with a total surface density of Co and Ni particles of 2.5×10 15 m -2 .
[0097] The method for preparing carbon nanotubes of this embodiment comprises the following steps: The layered metal catalyst was placed in a fixed bed reactor and 0.5 L / min natural gas was introduced at 800 °C for 100 min to prepare carbon nanotubes. After the reaction was completed, the temperature was lowered to room temperature under inert gas protection, and the black fluffy product was collected. The obtained carbon nanotubes grew in a single-walled array structure with a length of 1-5 μm.
[0098] Example 5 The preparation method of the layered metal catalyst of this embodiment comprises the following steps: (1) Dissolve 0.05 mol magnesium sulfate, 0.02 mol aluminum sulfate, 0.005 mol ferric nitrate, and 0.003 mol nickel nitrate in 1 L of water and stir to form solution A. Dissolve 0.001 mol sodium molybdate in water and stir to form solution B. Dissolve 1.1 mol urea in water and stir to form solution C.
[0099] (2) Solution A was directly added to solution C and mixed. The reaction temperature was set to 95 °C, the stirring speed was 100 rpm, the reaction was carried out for 3 h, and the end point pH was 8-11. Solution B was added dropwise to the mixed solution of A and C. The pH was still 8-11, and the stirring reaction was continued for 7 h under the same conditions. Subsequently, the mixture was aged at 95 °C for 36 h. After the reaction was completed, the product was filtered and washed to neutrality. The solid was dried at 80 °C in a forced air drying oven and ground to obtain a grid-like layered composite metal hydroxide with interlaced layers. The size of the layer assembly was 5-10 μm, and the bulk density of the powder was 0.04 g / cm 3 .like Figure 4 shown.
[0100] (3) 0.5 g of layered composite metal hydroxide was placed in a fixed bed reactor, 0.5 L / min nitrogen was introduced, the temperature was raised to 850 °C, calcined for 200 min, and then 0.2 L / min hydrogen was introduced for reduction for 10 min to obtain a layered metal catalyst with a total surface density of Fe and Ni particles of 4×10 15 m -2 .
[0101] The method for preparing carbon nanotubes of this embodiment comprises the following steps: The layered metal catalyst was placed in a fixed bed reactor and 0.5 L / min methane was introduced at 850 °C for 120 min to prepare carbon nanotubes. After the reaction was completed, the temperature was lowered to room temperature under inert gas protection, and the black fluffy product was collected. Figure 5 As shown, after the reaction, the catalyst still maintains a cross-grid structure, and carbon nanotubes grow in a single-walled mesh-like interwoven structure with a length of 1-3 μm in the space supported by the grid.
[0102] Comparative Example 1 The difference between this comparative example and Example 1 is that the reaction temperature in step (2) is adjusted to 10°C in this comparative example, and the other conditions are carried out according to the steps in Example 1. A composite metal hydroxide with an unformed sheet structure and severe stacking is obtained, such as Figure 6 As shown, it is almost impossible to catalyze the growth of carbon nanotubes in the subsequent step. This comparative example shows that the reaction temperature is too low to prepare a catalyst suitable for the growth of carbon nanotubes.
[0103] Comparative Example 2 The difference between this comparative example and Example 1 is that the stirring speed in step (2) is adjusted to 3000 rpm in this comparative example, and the other conditions are carried out according to the steps in Example 1. A composite metal hydroxide with severely stacked small flakes is obtained, and the flake size is only 1-5 nm, which is severely stacked into a micron-sized assembly. Due to the severe stacking, the catalyst flakes can only be vaguely seen in the thinner area at the edge of the assembly using a transmission electron microscope. Figure 7 shown.
[0104] The composite metal hydroxide was calcined and reduced, but the flakes were too small to withstand high temperatures, resulting in structural damage and almost no catalytic growth of carbon nanotubes. This comparative example shows that the stirring speed was too high and a catalyst suitable for the growth of carbon nanotubes could not be prepared.
[0105] Comparative Example 3 The difference between this comparative example and Example 1 is that the precipitation pH in step (2) is adjusted to 12, and the other conditions are carried out according to the steps in Example 1. A composite metal hydroxide with severely stacked small flakes is obtained, such as Figure 8 As shown. In the subsequent process, it is almost impossible to catalyze the growth of carbon nanotubes. This comparative example shows that the pH of the precipitation reaction is too high and a catalyst suitable for the growth of carbon nanotubes cannot be prepared.
[0106] Comparative Example 4 The difference between this comparative example and Example 1 is that in this comparative example, the metal ion concentration of solution A in step (1) is increased by 20 times to 3.6 mol / L, and the concentrations of solutions B and C are also increased by 20 times accordingly. The remaining conditions are carried out according to the steps in Example 1. A composite metal hydroxide with severely stacked small sheets is obtained, such as Fig. 9 As shown. In the subsequent process, it is almost impossible to catalyze the growth of carbon nanotubes. This comparative example shows that the metal ion concentration is too high and a catalyst suitable for the growth of carbon nanotubes cannot be prepared.
[0107] Comparative Example 5 The difference between this comparative example and Example 1 is that in this comparative example, the ammonium molybdate in step (1) is changed to boric acid, the stirring speed in step (2) is adjusted to 3000 rpm, and the other conditions are carried out according to the steps in Example 1. A composite metal hydroxide stacked with ultra-thin small sheets (sheet thickness is only about 1-2 nm, sheet size is 10-30 nm) is obtained, such as Fig.10 Among them, boric acid plays the role of interlayer dispersion, and the increase in rotation speed allows the precipitation to nucleate rapidly, thereby obtaining ultra-thin small sheets.
[0108] The composite metal hydroxide of this comparative example was calcined and reduced. Since the sheet layer was too thin, with a few layers or even a single layer structure, it could not withstand high temperature, and the sheet layer structure was completely destroyed, and it was completely unable to catalyze the growth of carbon nanotubes. This comparative example shows that the stirring speed is too high and the interlayer anions are changed, and it is impossible to prepare a catalyst suitable for the growth of carbon nanotubes.
[0109] Based on the above comparative examples and embodiments, it is explained that the reaction temperature is too low, the stirring speed is too high, the reaction pH is too high or the concentration of the reaction raw materials is too high, and the interlayer anions are changed, and catalysts suitable for the growth of carbon nanotubes cannot be prepared. The present invention can achieve the regulation of the assembly structure of layered composite metal hydroxides by regulating the preparation parameters, without the need to add additional template agents, etc. The preparation process is simple and easy to implement, and no cleaning additives are required, which is suitable for mass production; the regulation method of the present invention is widely applicable to binary, ternary, and quaternary layered composite metal hydroxide systems; the present invention can realize the stacking, partial stacking, cross-grid, and mutually discrete assembly structure of layered composite metal hydroxide sheets, and the exposure degree of a single sheet gradually increases, which can not only be used for the catalytic growth of relatively rigid multi-walled carbon nanotubes, but also can provide sufficient space for the catalytic growth of relatively flexible few-walled and single-walled carbon nanotubes; the process of producing carbon nanotubes by the layered composite metal hydroxide catalyst with controllable assembly structure described in the present invention is simple, the gas source is wide, and the applicable reactor types are rich.
[0110] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", "some implementation schemes" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0111] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a layered composite metal hydroxide, characterized in that: The following steps are involved: Mixing soluble divalent metal ions, soluble trivalent metal ions and soluble hexavalent metal acid radicals in a solvent, adjusting the pH to 6-11; reacting at 25-150°C; drying to obtain a layered composite metal hydroxide; The soluble hexavalent metal acid radicals include tungstate and / or molybdate; The blending is carried out under stirring conditions; the stirring speed is 1 rpm-600 rpm.
2. The method for preparing a layered composite metal hydroxide according to claim 1, characterized in that: The soluble divalent metal ions include Mg 2+ 、Zn 2+ , Ca 2+ , Mn 2+ , Fe 2+ 、Co 2+ 、Ni 2+ and Cu 2+ At least one of; and / or, The soluble trivalent metal ions include Cr 3+ 、Al 3+ 、Ru 3+ , Fe 3+ 、Co 3+ At least one of .
3. The method for preparing a layered composite metal hydroxide according to claim 1, characterized in that: The molar ratio of the soluble divalent metal ions to the soluble trivalent metal ions is (0.1-10): 1; The molar ratio of the soluble divalent metal ions to the soluble hexavalent metal acid radicals is (1-10): (0.001-1).
4. The method for preparing a layered composite metal hydroxide according to claim 1, characterized in that: The reaction time is 0.1 h-36 h.
5. The method for preparing a layered composite metal hydroxide according to claim 1, characterized in that: The soluble divalent metal ions include a first soluble divalent metal ion and a second soluble divalent metal ion; The first soluble divalent metal ion includes Fe 2+ 、Co 2+ 、Ni 2+ and Cu 2+ At least one of; The second soluble divalent metal ion comprises Mg 2+ 、Zn 2+ , Ca 2+ , Mn 2+ At least one of; and / or, the soluble trivalent metal ions include a first soluble trivalent metal ion and a second soluble trivalent metal ion; The first soluble trivalent metal ion includes Ru 3+ , Fe 3+ 、Co 3+ At least one of; The second soluble trivalent metal ion includes Cr 3+ 、Al 3+ At least one of .
6. The method for preparing a layered composite metal hydroxide according to claim 5, characterized in that: The molar ratio of the first soluble divalent metal ion to the second soluble divalent metal ion is (0.002-1):1; and / or, The molar ratio of the first soluble trivalent metal ion to the second soluble trivalent metal ion is (0.002-1):
1.
7. The layered composite metal hydroxide obtained by the method for preparing a layered composite metal hydroxide according to any one of claims 1 to 6; the layered composite metal hydroxide has a sheet diameter of 0.5 μm to 10 μm; and / or, The thickness of the layered composite metal hydroxide is 5 nm to 200 nm; and / or, The bulk density of the layered composite metal hydroxide is 0.01 g / cm 3 -0.20 g / cm 3 .
8. A method for preparing a layered metal catalyst, characterized in that: The following steps are involved: The layered composite metal hydroxide obtained by any one of the preparation methods of claims 1 to 6 or the layered composite metal hydroxide according to claim 7 is calcined at a heating rate of 1°C / min-20°C / min to 400°C-1000°C, and then reduced to obtain a layered metal catalyst.
9. The method for preparing a layered metal catalyst according to claim 8, characterized in that: The calcination time is 20 min -1440 min; and / or, The reduction time is 1 min-60 min.
10. A layered metal catalyst obtained by the method for preparing a layered metal catalyst according to any one of claims 8 to 9; the layered metal catalyst has a sheet diameter of 1 μm to 50 μm; and / or, The surface density of the metal particles supported on the layered metal catalyst is 10 12 m -2 -10 16 m -2 .
11. A method for preparing carbon nanotubes, characterized in that: The following steps are involved: Decomposing a carbon source at 500°C-1000°C to deposit carbon nanotubes on a layered metal catalyst prepared by the method for preparing a layered metal catalyst according to any one of claims 8-9; removing the layered metal catalyst to obtain carbon nanotubes; the carbon nanotubes have a length of 0.5-50 μm.
Citation Information
Patent Citations
Hydrotalcite like catalyst, preparation method and application thereof
CN103816929A
Layered bimetal hydroxide preparation method, and product prepared therethrough
CN107128879A
Preparation method of carbon nanotube catalyst, and carbon nanotube
CN111495380A
Method for producing iron-based layered double hydroxides and oxides
EP4201512A1
Process for manufacturing an absorbent composition
US5843862A